Comparability of some generalization of the inverse Bernstein theorem to F -spases - H. A. Voloshyn; V. K. Maslyuchenko (Математичні Студії, 2011)
We shove that our generalization of the inverse Bernstein theorem to F -spases and Svedov's generalization of this theorem are not comparable.